Synthesis of Poly(NIPAM) for Efficient Trypsin Purification Using Affinity Precipitation Technique - Syaubari, Syaubari; Bachtiar, Dandi; Sabrina, Nur Irhamni; Adhi, M Furqan (Reaktor, 2024)
The method of bio specific affinity for separation has gained attention and continues to be developed today. The affinity precipitation technique is continuously being refined because it is simpler, less complex, and highly economical without reducing product purity. Moreover, the obtained polymers can be reused and easily scaled up. The polymer used for affinity precipitation has functional groups that can act specifically, making it known as a “smart polymer.” The hydrophilic polymer and soluble liquid can be replaced with hydrophobic ones, becoming insoluble under certain conditions such as changes in pH, temperature, ionic strength, or the addition of reagents. This study aims to utilize ligand pairs for soluble liquid polymers based on macro ligands that are easily developed for large-scale applications. The research was conducted in two stages and is ready for enzyme purification testing. First, the synthesis of NIPAM polymer was carried out, with NIPAM and AIBN as fixed variables, while MPA served as the variable. Second, PABA conjugation was performed, where the synthesized NIPAM polymer was conjugated with the PABA ligand, making PABA characterization the changing variable in this phase. The dry weight of carboxylated Poly(NIPAM) obtained was 91.3%, carboxylated Poly(NIPAM)-co MPA 0.4 was 90.4%, and carboxylated Poly(NIPAM)-co MPA 0.6 was 88.9%. In the SEM test, the morphological structure of Poly(NIPAM) showed relatively harder surfaces. In the FTIR test, a significant change was observed in the spectra at 3300-2500 cm-1, which became weaker due to the presence of carboxyl groups characterized in Poly(NIPAM). The spectrophotometer test revealed the LCST condition at a temperature of 40°C. The conjugation of PABA onto Poly(NIPAM)-co-MPA 0.6 with 50 mg PABA showed better conjugation efficiency, with a conjugation yield of 52.6%. Incorporation of PABA shows recovery of trypsin between 65-80 %.